The influence of cardiovascular training methods and level of training on the fitness level of futsal referees - Andrianto, Sigit Dwi; Nopembri, Soni; Subagyo; Laksmi Ambardini, Rachmah; Gusdernawati, Aulia (SPORT TK-EuroAmerican Journal of Sport Sciences, 2024)
This study aimed to apply cardiovascular training, specifically through intensive interval and extensive interval training methods, to enhance the fitness levels of AFP DIY futsal referees in Indonesia. The study design was quasi-experimental with a 2x2 factorial design. The research subjects were 36 male AFP DIY futsal referees aged 25-35 years. The training test instrument used the Heart Rate Recovery Test (HRRT) and the referee fitness instrument used the FIFA Assistant Referee Intermittent Endurance Test (ARIET). The software used for data analysis was SPSS version 21.0 for Windows. The results indicated that cardiovascular training methods significantly impact the fitness levels of futsal referees (p<0.05). The intensive interval training method positively influenced the fitness of futsal referees (p<0.05). Similarly, the extensive interval training method also had a positive effect on improving the referees’ fitness (p<0.05). The group that received the extensive interval training showed greater improvements compared to the intensive interval group, with an increase of 43.48%. Furthermore, there is an interaction between cardiovascular training methods, training levels, and fitness levels (p<0.05). These findings offer valuable insights for futsal referees, emphasizing the importance of selecting the most effective training methods to enhance their fitness levels.